IMPROVING THE FOURTH-GRADE STUDENTS’ ACHIEVEMENT IN WRITING PROCEDURE TEXT AT SDN MOJOTENGAH I SUKOREJO BY USING PICTURE MEDIA - Aqidatul Islamiyah,; Dwi Kameluh Agustina; Sripit Widiastuti (JOSAR (Journal of Students Academic Research), 2020)
fourth grade students at SDN Mojotengah I Sukorejo remains low with mastery learning reaching 10.53% and not fulfilling the KKM, that is, 80%. This is due to the difficulty in writing procedure textstudents to catch information clearly, compared to the information expressed through wordsimprove fourth grade students’ achievement in writing procedure text at SDN Mojotengah I Sukorejo by using picture media. This research was a classroom action research. The data were analyzed quantitatively. Meanwhile, the data were collected by using writtenResults indicated an improvement in students’ writing achievement on content and language aspects thanks to the use of picture media. Thus, it is clear that picture media improved fourth grade students’ achievement in writing procedure text at SDN Mojotengah I Sukorejo. Teachers are suggested to use more varied pictures in writing procedure text activity. Future researchers are expected to develop innovative and effective learning media to enhance the quality of learning process.